456. Implementing an At-Home Smell Test for Early Assessment of COVID-19 in High-Risk Healthcare Workers. (31st December 2020) - Weiss, Julian J; Attuquayefio, Tuki; White, Elizabeth B; Geng, Bertie; Handoko, Ryan; Herz, Rachel S; White, Theresa L; Iwasaki, Akiko; Grubaugh, Nathan D; Datta, Rupak; Campbell, Melissa; Martinello, Richard A; et al.
Abstract: Background: Smell loss has been recognized as an important, and potentially early, sign of COVID-19. However, to date smell loss has only been assessed in retrospective, COVID+ cohorts, and largely through self-report. The objective of this study was to implement a daily standardized behavioral test of smell sensitivity in healthcare workers (HCW) to capture changes in smell sensitivity over time and to assess whether these changes occur prior to positive COVID test. Methods: The study enrolled 500 high-risk COVID-negative HCW during the COVID-19 epidemic in Connecticut, beginning March 28, 2020 (80% F, mean age 38, 58% nurses). Initially, HCW received a daily symptom questionnaire with parosmia screening questions. On April 23 we introduced the "Jiffy", a daily at-home psychophysical test of smell sensitivity, where olfactory stimuli are sampled and rated for perceived intensity. SARS-CoV-2 infection was tested every three days by PCR of nasopharyngeal swabs or saliva. Screening Questionnaire for Parosmia The "Jiffy" Survey and Test Results: Of the first 500 enrolled HCW, 376 HCW (75%) completed the Jiffy 4528 times (mean 12 times/HCW). 17/500 HCW (3.4%) had a COVID+ test, of which 9/17 (53%) reported smell loss through the Jiffy or the daily symptom survey. 6/9 (67%) reported smell loss that preceded or was concurrent with a COVID+ test. 8/17 COVID+ HCW completed the Jiffy, with 5/8 (63%) reporting reductions in smell versus 42/368 (11%) COVID- HCW (OR=13, 95% CI: 2.4–85, p =.001). COVID+ HCW rated their greatest reduction in smell sensitivity as slight (40%) and severe (60%), versus slight (88%) and moderate (12%) in COVID- HCW. 16/17 COVID+ HCW completed a daily symptom survey (mean 14 times/HCW), with 8/16 (50%) ever reporting parosmia versus 90/466 (19%) of COVID- HCW (OR=4.2, 95% CI: 1.3–13, p =.007). Overall, parosmia was the first reported symptom in 3/13 (23%) COVID+ HCW who reported symptoms. Smell Changes in COVID+ and COVID- HCW Reported in the "Jiffy" Test Smell Changes in COVID+ and COVID- HCW Reported in Daily Symptom Questionnaire Smell Changes among COVID+ HCW by Day, Relative to Day of Positive PCR Test Conclusion: We conducted a prospective study of smell testing in a population at high risk for COVID-19 using two parallel approaches. Our results demonstrate the feasibility of at-home smell testing for assessing parosmia during COVID-19, in some cases even prior to a positive PCR result. Given the urgent need for widespread, low-cost, non-invasive testing for COVID-19, we are now developing an easy-to-use app to distribute this survey more widely to high-risk populations. Disclosures: Julian J. Weiss, BA, Nothing to disclose